2001
DOI: 10.1023/a:1017996113871
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Atrial natriuretic peptide (ANP) was originally isolated from cardiac atria, and has potent natriuretic, diuretic, and vasorelaxant properties. It has been localized in neurons and astrocytes in the cerebral cortex and the white matter. We hypothesize that glial ANP may contribute to the regulation of cerebral blood flow in brain infarction. In order to elucidate this possible role, the immunohistochemistry of ANP was studied in cases of brain infarction and in other cases of brain trauma for comparison. A sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…[1011] Our study showed that BNP in patients was significantly higher than in controls ( P < 0.001) which is in agreement with studies in the past. [1213] One of the reasons postulated for raised BNP levels in stroke patients is cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…[1011] Our study showed that BNP in patients was significantly higher than in controls ( P < 0.001) which is in agreement with studies in the past. [1213] One of the reasons postulated for raised BNP levels in stroke patients is cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Natriuretic peptides have been shown to be elevated in patients with SAH and have been found to be associated with a decreased level of consciousness [17,18]. Data from experimental studies suggest that cerebral ischemia induces ANP release [6,7]. In patients with ICH, higher levels of brain natriuretic peptide, another member of the natriuretic peptide family, have been reported to be associated with functional neurological outcome [19].…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for about 98% of all circulating natriuretic peptides, ANP is released from intracellular granules in atrial myocytes upon atrial dilation, with myocyte stretching through volume and blood pressure challenge being the most potential stimulators [5]. ANP-immunoreactive glial cells have been found in ischemic brain tissue, suggesting regulation of cerebral blood flow through ANP [6]. Moreover, release of ANP from brain tissue has also been reported during cerebral ischemia [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BNP increase has been associated with the intensity of brain ischemia reflecting the magnitude of brain injury [4,7]. On the other hand, an acute blood pressure elevation has been well documented during the acute phase of stroke and it might indeed increase BNP released from the heart, as BNP plays a role in the hemodynamic regulation during this period [8].…”
Section: Discussionmentioning
confidence: 99%